2017
DOI: 10.17245/jdapm.2017.17.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment in patients with severe gag reflex using propofol-remifentanil intravenous sedation

Abstract: Patients with severe gag reflex (SGR) have difficulty getting the treatment they require in local clinics, and many tend to postpone the start of their treatment. To address this problem, dentists have used behavioral techniques and/or pharmacological techniques for treatment. Among the pharmacological methods available, propofol IV sedation is preferred over general anesthesia because it is a simpler procedure. Propofol in combination with remifentanil is characterized by stable sedative effects and quick rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The combination of propofol and remifentanil has been previously described for dental sedation [2][3][4], but many of these papers describe fixed-dose regimes, especially for the narcotic base. Coskun, et al, [5] described the combined use of TCI propofol and remifentanil for ovarian oocyte retrieval but used lower remifentanil target levels at the commencement than those that we utilised, in a surgical procedure expected to be far less stimulating than dental surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of propofol and remifentanil has been previously described for dental sedation [2][3][4], but many of these papers describe fixed-dose regimes, especially for the narcotic base. Coskun, et al, [5] described the combined use of TCI propofol and remifentanil for ovarian oocyte retrieval but used lower remifentanil target levels at the commencement than those that we utilised, in a surgical procedure expected to be far less stimulating than dental surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With the constant drug levels provided by the Alaris PK TCI system, a commensurately constant depth of sedation is produced. An additional advantage of the addition of remifentanil to propofol sedation is the suppression of the gag reflex [2].…”
Section: Sci Forschenmentioning
confidence: 99%
“…Owing to propofol's limited analgesic properties, a higher dose of propofol is required as a single anesthetic agent to reduce pain-induced movement, which may lead to deeper level sedation and longer recovery time. Several studies have reported that combining different types of drugs has synergistic effects on drug sedative potential [ 13 14 ]. Therefore, the addition of opioid narcotics reduces the required dose of propofol significantly [ 15 16 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The combination of remifentanil and propofol has a synergistic effect, which can reduce the dose of propofol to 75%, and propofol has no effect on the clearance rate of remifentanil. 15,16 This study showed that the incidence of adverse reactions such as nausea and vomiting, chills, restlessness, cough, and tachycardia was lower in the observation group than that in the control group. It suggested that the safety of remifentanil combined anesthesia is higher than that of fentanyl combined anesthesia.…”
Section: Discussionmentioning
confidence: 89%